Impact of Vegetable Oil Type on the Rheological and Tribological Behavior of Montmorillonite-Based Oleogels - M. A. Martín-Alfonso; José F. Rubio-Valle; Juan P. Hinestroza; José E. Martín-Alfonso (Gels, 2022)
We formulated and characterized oleogels based on montmorillonite clay and vegetable oils that could serve as eco-friendly semi-solid lubricants. In particular, we studied the influence of the physical-chemical properties of olive, castor, soybean, linseed, and sunflower oils on the rheological, chemical, thermal, and tribological properties of the semi-solid lubricants. We prepared the oleogels via the highly intensive mixing of vegetable oils with clay at a concentration of 30 wt.%. The oleogels exhibited shear-thinning, thixotropy, structural recovery, and gel-like behavior commonly related to that of a three-dimensional network. The results were corroborated via XRD measurements showing the presence of intercalated nanoclay structures well-dispersed in the vegetable oil. Empirical correlations between the content of saturated (SFAs), unsaturated (UFAs), mono-unsaturated (MUFAs) and poly-unsaturated (PUFAs) fatty acids and the plateau modulus of the aerogels were found. From these experimental results, we can conclude that the fatty acid profile of the vegetable oils exerts an important influence on the rheological and tribological properties of resulting clay and vegetable oil oleogels.